1980
DOI: 10.1007/bf00775405
|View full text |Cite
|
Sign up to set email alerts
|

Organization, replication and modification of the human genome: Synthesis and methylation of palindromic, repeated and unique hela nDNA sequences during the S-phase

Abstract: At least five supermethylated nDNA families have been found in HeLa cells. The concentration of 5-methylcytosine increases on palindromes from 1 to 5 hours during the nDNA duplicative phase, decreasing again at the 6th hour of S. The early S-phase involves the accumulation of 5-methylcytosines on the nDNA sequences reassociating near a Cot = 3 x 10(-1). Late S involves increment of this base on the sequences which reassociate near a Cot = 9 x 10(-1) and Cot = 7 x 10(1). The unique sequences show a moderate met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
6
0
1
Order By: Relevance
“…We have shown elsewhere for HeLa cells that palindromes are methylated during the S-phase in parallel with methylation of total DNA, while their methylation pattern is much higher than that of total DNA [5]. This is strikingly confirmed by the present study which involved other cell species.…”
Section: Hypermethylation Of Palindromes In Nuclei Isolated From Growsupporting
confidence: 91%
See 4 more Smart Citations
“…We have shown elsewhere for HeLa cells that palindromes are methylated during the S-phase in parallel with methylation of total DNA, while their methylation pattern is much higher than that of total DNA [5]. This is strikingly confirmed by the present study which involved other cell species.…”
Section: Hypermethylation Of Palindromes In Nuclei Isolated From Growsupporting
confidence: 91%
“…Then, as expected, the kinetics of reassociation showed that the h~omethylated DNA is mainly made up of unique sequences, while the hypermethylated DNA is made up of repetitive and palindromic sequences IS]. The palindromic sequences reach a specific methylation, during the S-phase, which is much higher than that of the repetitive sequences [5]. However, a decrease of transcription corresponds, in the Sphase, to the hypermethylation of this DNA class and of total DNA [5-73. This investigation shows increased methylation of total and palindromic DNAs of transformed cells relative to untransformed cells.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations